Synthesis, Structure, Spectroscopic and Redox Properties of Copper(II)-N Complexes: Crystal and Molecular Structure of Bis(N-3,5 Phenylsalicylaldininato)copper(II) - Kasumov, V.T.; Bulut, A.; Köksal, F.; Aslanoǧlu, M.; Uçar, I.; Kazak, C. (Elsevier Ltd, 2006)
New bulky bis(N-3,5-Bu2tphenyl-R-salicyaldiminato)copper(II) complexes X were synthesized and characterized by analytical, spectroscopic (IR, UV/Vis, EPR), electrochemical methods, and their chemical redox reactivity were studied. X-ray structural analysis of 1 revealed that the CuN2O2 coordination core forms a distorted square-planar geometry with a cis-N 2O2 donor set which is not expected for analogous complexes. The UV/Vis and EPR results indicate that X complexes have a tetrahedrally distorted square-planar structure in the solid state and in solution. In the chemical oxidation of X by (NH4) 2Ce(NO3)6 along with disappearance of their EPR spectra, the appearance of new Cu(II) patterns at g = 2.169-2.189 for all X and radical signals in the cases of 5 and 6 were detected. The chemical reduction of some X complexes was accompanied by the disappearance of their EPR signals. The separation in peak potentials (ΔEp) for complexes X are in order 4 < 3 < 2 < 1 < 6. The electrochemical results suggested that the complex 4 has the highest electrochemical rate assuming both the Cu(II) and Cu(I) forms appear in a similar geometrical configuration, so the electron transfer does not require larger reorganization of the complex in complex 4. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Bulky Salicylaldiminato-Cu(II) Complexes; Chemical Redox Behaviors; Electrochemistry; Spectroscopy; X-Ray Crystal Structure